Afforestation in the State of Bihar - Mishra, P. (Indian Forester, 1957)
The extent of forests under scientific management before and after the enforcement of the Bihar Private Forests Act and the need to make up the deficiency by afforestation has been indicated. The afforestation schemes in the State Second plan with allotments and the targets have been explained. Finally the technique' of afforestation adopted and some experience acquired has been described.